Late Iron Age longhouse chronology: A study aimed at constructing a formal house chronology for the Late Iron Age, based on selected localities in central and eastern Jutland - Laursen, Stine Vestergaard; Holst, Mads Kähler (Danish Journal of Archaeology, 2017)
This paper presents a formalised chronological study of the longhouses of the Late Iron Age. This is based on the correspondence analysis of data relating to house ground plans recorded at a number of Iron Age settlements in central and eastern Jutland, which, as a region, has the most comprehensive relevant data set, including many constructional details. The chronology constitutes a formalisation of the house-chronological considerations undertaken to date in reference to settlements in Jutland and results in a seriable sequence, the chronological significance of which is supported by stratigraphic observations. The study demonstrates that, in general, the investigated settlements follow the same chronological development and can therefore be correlated. Moreover, it shows that the placing of each individual house in the chronology is subject to some uncertainty, due to the relatively small number and long duration of the chronological features.